2013
DOI: 10.1371/journal.pntd.0002036
|View full text |Cite
|
Sign up to set email alerts
|

Symptomatic and Asymptomatic Campylobacter Infections Associated with Reduced Growth in Peruvian Children

Abstract: BackgroundAlthough diarrheal illnesses are recognized as both a cause and effect of undernutrition, evidence for the effect of specific enteropathogens on early childhood growth remains limited. We estimated the effects of undernutrition as a risk factor for campylobacteriosis, as well as associations between symptomatic and asymptomatic Campylobacter infections and growth.Methodology/Principal FindingsUsing data from a prospective cohort of 442 children aged 0–72 months, the effect of nutritional status on th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
147
1
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 126 publications
(153 citation statements)
references
References 31 publications
4
147
1
1
Order By: Relevance
“…[4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21]41 These risk factors were on water, sanitation, hygiene, and knowledge of the causes of childhood diarrheal disease and prevention. All of these variables were obtained from the baseline KPC survey administered to the primary caregiver in each household.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…[4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21]41 These risk factors were on water, sanitation, hygiene, and knowledge of the causes of childhood diarrheal disease and prevention. All of these variables were obtained from the baseline KPC survey administered to the primary caregiver in each household.…”
Section: Methodsmentioning
confidence: 99%
“…For Campylobacter, maternal education and household water connection were found to be significant risk factors for this age group. 12 In Blake and others, where five enteric pathogens were compared differences were observed in risk factors between pathogens for children 5 years of age. For example exclusive breastfeeding was protective for shigella, however not for rotavirus or enterotoxigenic Escherichia coli.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…19 This is also consistent with findings from Lee and others who reported that asymptomatic Campylobacter infections were associated with significant reductions in weight gain over a 3-month period. 20 In rural Gambia infants had diarrhea 7.3% of the time, however, elevated lactulose:mannitol (L:M) ratios in urine, a measure of impaired intestinal barrier function, were observed in infants 76% of the time. Furthermore, it was estimated that L:M ratios in this population could predict 43% of observed variation in length growth and 39% of weight growth.…”
Section: Introductionmentioning
confidence: 99%
“…Campylobacter is often shed for extended periods following such episodes, and asymptomatic excretion is common (11). The prevalence and consequences of these infections on childhood development are unclear, though recently, not only symptomatic Campylobacter infection but also asymptomatic Campylobacter infection has been associated with poor early-childhood weight gain in Peru (12).…”
mentioning
confidence: 99%